Breaking the scaling relationship via dual metal doping in a cobalt spinel for the OER: a computational prediction. Issue 33 (17th August 2020) - Kang, Yikun; Zhang, Feiran; Liu, Bowen; Sun, Yuanqing; Zhang, Xiao; Song, Weiyu; Wei, Yuechang; Zhao, Zhen; Liu, Jian
Abstract : The scaling relationship in the OER is found to be broken on a reconstructed Co3 O4 (110) surface via dual metal doping. Abstract : The lower limit of overpotential derived from the scaling relationship in the generally proposed adsorbate evolution mechanism (AEM) greatly hinders the oxygen evolution reaction (OER) activity in electrochemical energy conversion. The lattice oxygen mechanism tends to be triggered on oxygen-enriched surfaces under in situ conditions; however, the required specific geometry and electronic structure need in-depth exploration. Here, tunable Co3 O4 is used as a model material, where the reconstruction of dominantly exposed (110) surface under reaction conditions is first presented using an ab initio thermodynamic approach. We found the geometry of the neighboring oxygen on the reconstructed surface, and oxidized Co 3+ with five-fold coordination (Co3+5f) was identified as the active site. A total of 23 metal doping types were employed based on the reconstructed surface. We showed that the OER process with lattice oxygen participating can lead to favorable thermodynamics by the doping of early transition metals, and the O–O coupling of surface lattice oxygen can be facilitated kinetically by dual doping with Zn. Considering both thermodynamics and kinetics, the dual doping of Zn–Cr exhibits theoretical OER activity beyond the conventional AEM limitations and is suggested to be a candidate with enhanced OER performance. Moreover, we demonstrated that the dual doping with Zn enhances metal–oxygen covalency, where the moderate activity of the surface lattice oxygen is required for feasible O–O coupling kinetics while retaining favorable thermodynamic propensity.